"Children of the Soil" to "Dark Wind": Nature, Environment and Climate in Indian Films. Issue 1 (1st January 2023) - Jain, Pankaj; Sharma, Shikha
Abstract : India is widely known as the biggest producer of films, now globally known with the portmanteau "Bollywood." India also grabs the media attention for another reason—climate change. In 2015, The New York Times published an op-ed with a cartoon showing India as the proverbial "elephant" blocking the progress at the Paris Climate Change Conference. With the staggering number of films India produces and the steady increase in climate change-related disasters that India faces, the critics embraced the film Kadvi Hawa (literally, Dark Wind or Bitter Wind, 2017) as the "pioneering" film raising the critical issue of climate change. However, the issues raised in the movie were amply dealt with in several other Indian films in the last several decades. This article is a survey of Indian films that have shown or dealt with nature, environment, or climate starting from the 1940s till the present time.